Performance modeling and prediction of enterprise JavaBeans with layered queuing network templates. - Xu, Jing (Software engineering notes.)
Component technologies, such as Enterprise Java Beans (EJB) and .NET, are used in enterprise servers with requirements for high performance and scalability. This work considers performance prediction from the design of an EJB system, based on the modular structure of an application server and the application components. It uses layered queueing models, which are naturally structured around the software components. This paper describes a framework for constructing such models, based on layered queue templates for EJBs, and for their inclusion in the server. The resulting model is calibrated and validated by comparison with an actual system.